Public goods and public policy: what is public good, and who and what decides? - Hazelkorn, E; Gibson, A (Centre for Global Higher Education, University of Oxford, 2017)
Professor Ellen Hazelkorn and Andrew Gibson from Dublin Institute of Technology ask how we should determine higher education’s contribution to society.